Placement of 131Cs permanent brachytherapy seeds in a large combined cavity of two resected brain metastases in one setting: case report and technical note - Greenwald, Jacelyn; Taube, Shoshana; Yondorf, Menachem Z.; Smith, Andrew; Sabbas, Albert; Wernicke, A. Gabriella (Journal of Contemporary Brachytherapy, 2019)
Large brain metastases are presently treated with surgical resection and adjuvant radiotherapy. However, local control (LC) for large tumors decreases from over 90% to as low as 40% as the tumor/cavity increases. Intraoperative brachytherapy is one of the focal radiotherapy techniques, which offers a convenient option of starting radiation therapy immediately after resection of the tumor and shows at least an equivalent LC to external techniques. Our center has pioneered this treatment with a novel FDA-cleared cesium-131 ( 131 Cs) radioisotope for the resected brain metastases, and published promising results of our prospective trial showing superior results from 131 Cs application to the large tumors (90%). We report a 57-year-old male patient, with metastatic hypopharyngeal brain cancer. The patient presented with two metastases in the right frontal and right parietal lobes. Post-resection of these lesions resulted in a large total combined cavity diameter of 5.3 cm, which was implanted with 131 Cs seeds. The patient tolerated the procedure well, with 100% local control and 0% radiation necrosis. This case is unique in demonstrating that the 131 Cs isotope was not only a convenient option of treating two resected brain metastases in one setting, but also that this treatment option offered excellent long-term LC and minimal toxicity rates.